Groundcovers Improve Soil Properties in Woody Crops Under Semiarid Climate - Blanca Sastre; Omar Antón-Iruela; Ana Moreno-Delafuente; Mariela J. Navas; Maria Jose Marques; Javier González-Canales; Juan Pedro Martín-Sanz; Rubén Ramos; Andrés García-Díaz; Ramón Bienes (Agriculture)
There is a worldwide need to enhance soil health, particularly in agricultural areas. Groundcovers are widely recognized sustainable land management (SLM) practices that improve soil health and provide climate benefits by sequestering atmospheric carbon. A paired-plots study was carried out in woody crops (17 sites, olive groves and vineyards) in a semiarid area of central Spain to measure soil parameter changes induced by different management practices in the medium term. The selection across different locations aimed to determine whether the impact of groundcovers was substantial enough to produce significant changes in the studied soil parameters, even when accounting for variations in soil types. Each site consisted of neighboring plots: One was managed with conventional tillage (CT). The other was managed with an alternative soil management practice: (1) spontaneous groundcovers (GC) or (2) no soil management (NM). Vegetation and soil parameters were measured in spring 2021. Despite the low aboveground biomass in GC (77 g m−2), this treatment improved soil organic carbon stock (+4.4 Mg ha−1), infiltration rate (+50%), and aggregate stability (+35%) compared to CT, but higher compaction along the profile was detected. NM only resulted in a better infiltration rate, with high soil compaction. Our study provides supplementary information to long-term studies, which may include soil biological parameters as soil health indicators and yield response. Outcomes of these soil assessments lend support to the implementation of agricultural policies that promote GC as a SLM practice, in order to extend this technique to woody crops.